Interconnected activisms in a city under socio-spatial fragmentation - Gustavo Nagib; Katia A. Nakayama (lo Squaderno)
São Paulo, the largest South American metropolis, is the material and symbolic expression of a complex intertwining of socio-spatial processes that reveal a set of contradictions linked to the city’s production logic. These include segregating planning, visible and invisible barriers between territories and social classes, contrasts in aesthetic and environmental standards among neighborhoods, extensive peripheries lacking basic urban infrastructure and services, degradation of the historic center, idle properties that fail to fulfill the social function of property, environmental degradation of rivers, cyclical water crises, precarious maintenance of public spaces, poor spatial distribution of parks and cultural and sports facilities, tangled electricity and telecommunications wires exposed to the elements, prioritization of highway-based urban planning and individual transportation, slums and other precarious housing, urban mobility challenges, violence, prejudices (such as racism, homopho- bia and sexism), air and noise pollution, and the speculative real estate market. However, beyond these typical characteristics of contradictory urbanization, it is also possible to identify a set of actions and spaces of resistance that redefine metropolitan forms and content.